Fat snook performance at different rearing temperatures - Bendhack, Fabiano; Peczek, Viviane; Gonçalves, Rafaela; Baldan, Ana Paula (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to quantify the growth of juvenile fat snook (Centropomus parallelus) reared at different temperatures. The fish were cultured during 49 days at 20, 23, 26, and 29°C. Water temperature influenced weight gain. Fish reared at 26 and 29°C showed the greatest weight gains and were more efficient in feed conversion. Fish reared at 29°C also showed the best specific growth rates. Fat snook performance is affected at 20°C, and the species should be grown at temperatures above 23°C.